2019
DOI: 10.1111/jdi.13132
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between glycated hemoglobin level and duration of hypoglycemia in type 2 diabetes patients treated with sulfonylureas: A multicenter cross‐sectional study

Abstract: Aims/Introduction Sulfonylurea‐related hypoglycemia increases the risk of cardiovascular sequela, such as cardiac arrhythmia. This study aimed to clarify the relationship between the level of glycated hemoglobin (HbA1c) and the duration of hypoglycemia in type 2 diabetes patients treated with sulfonylureas. Materials and Methods Glucose levels in the enrolled patients (n = 300) were investigated with a professional continuous glucose monitoring device in the outpatient setting at six diabetes centers in Japan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…In Japan, insulin dose titration for type 2 diabetes is generally physician‐led, and poor patient concordance with insulin regimens is acknowledged as an issue 20 . Most participants (92%) in the current study used fixed insulin doses; 17% dose‐adjusted for the current glucose level and 14% for their meals.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In Japan, insulin dose titration for type 2 diabetes is generally physician‐led, and poor patient concordance with insulin regimens is acknowledged as an issue 20 . Most participants (92%) in the current study used fixed insulin doses; 17% dose‐adjusted for the current glucose level and 14% for their meals.…”
Section: Discussionmentioning
confidence: 98%
“…Information on the frequency of hypoglycemia during treatment of diabetes in non-Western countries is limited [18][19][20] , and hypoglycemia is a great concern for patients using insulin in Japan 21 . In the present study, a low level of hypoglycemia was observed at baseline, and 27% of participants did not experience glucose levels <70 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, for diabetes there are several options for patients. Sulfonylureas are a class of drugs that needs dose adjustment or discontinuation due to the inherent risk of hypoglycemia when given to non-COVID-19 patients [ 93 ]. Since CYP2C9 enzyme and CAR (receptor regulating the enzyme) are affected by COVID-19-related inflammation [ 84 ], it is likely that sulfonylureas will accumulate, leading to more severe hypoglycemia.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%